Strengthening screw shaft measurement system in teaching factory through measurement system analysis: A case study - Sumasto, Fredy; Samudra, Bayu; Hakim, Ali Rachman; Imansuri, Febriza; Pratama, Indra Rizki (Universitas Sultan Ageng Tirtayasa, 2025)
Ensuring accurate measurement of precision components is critical in the automotive industry. This study investigates measurement challenges for screw shaft components at the Teaching Factory of Politeknik STMI Jakarta. The initial measurement system performed poorly, with 100% total variation attributed to measurement error and a Number of Distinct Categories (Ndc) of 1, indicating an inability to distinguish product variations. To address this, a Measurement System Analysis (MSA) using the Gage Repeatability and Reproducibility (GRR) method was conducted. Improvements, including operator training, regular calibration, and a custom jig fixture, were implemented. As a result, the GRR value decreased to 26.27%, with repeatability contributing 25.40% and reproducibility 6.74%. The Ndc value increased to 5, reflecting improved capability to differentiate product variations. These outcomes demonstrate that MSA is an effective strategy for evaluating and enhancing measurement systems. It is particularly valuable in vocational education settings to ensure measurement reliability, maintain quality standards, and support industry-relevant skill development.